Changing Fortunes: An analysis of the dynamics of income inequality in US metropolitan areas - Cavanaugh, Alicia; Breau, Sébastien (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2019)
Income inequality has increased significantly in OECD countries over the last few decades. Rising inequality has been particularly pronounced in the United States, especially so in metropolitan areas. During this time, the increasingly uneven distribution of income reflects the pulling away of high-income earners, as well as increased returns to skilled workers. This study uses IPUMS data to build a novel dataset for 226 MSAs over the 1980 to 2010 period. Results suggest that education has had the strongest impact on rising inequality across US metropolitan areas. Our findings also suggest that supply-side factors such as racial segregation and the size of the immigrant population are likewise positively linked with greater inequality.